Performing the Self in Digital Spaces: Understanding Dual Instagram Accounts through Dramatism and Media Ecology Perspectives - Ainy Nurul Qoyyimah (Universitas Telkom, 2025)
This study explores how Indonesian Instagram users construct and negotiate their digital identities through the use of two accounts commonly known as the first account and the second account. Using Kenneth Burke's dramatism and Marshall McLuhan's media ecology as theoretical frameworks, the study investigates the symbolic and environmental dimensions of online self-presentation. The study adopts a qualitative approach combining content analysis and semi-structured interviews with five active Instagram users who maintain public and private accounts. The findings reveal that users perform distinct identities in these two spaces: the first account serves as a stage for curated, professional, and aesthetically controlled self-representation, while the second account serves as a more intimate and expressive arena for personal narratives and emotional disclosure among a trusted audience. Through Burke's pentadic analysis, these practices are understood as symbolic acts shaped by social expectations and platform affordances. From a media ecology perspective, Instagram's visual and interactive architecture reinforces distinct modes of communication that shape users' identity performances. This study contributes to broader discussions on digital identity and self-presentation by demonstrating how technological environments mediate symbolic expression and the negotiation of privacy in everyday social media practices. This study also highlights the growing importance of multiple account culture as a coping mechanism for navigating authenticity, visibility, and social pressures in digital society.